Proceedings of the 14th EAI International Conference on Mobile and Ubiquitous Systems: Computing, Networking and Services 2018
DOI: 10.4108/eai.7-11-2017.2273696
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Person Brain Activity Recognition via Comprehensive EEG Signal Analysis

Abstract: An electroencephalography (EEG) based brain activity recognition is a fundamental eld of study for a number of signi cant applications such as intention prediction, appliance control, and neurological disease diagnosis in smart home and smart healthcare domains. Existing techniques mostly focus on binary brain activity recognition for a single person, which limits their deployment in wider and complex practical scenarios. erefore, multi-person and multi-class brain activity recognition has obtained popularity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…The brain function's electromagnetic patterns can be detected using non-invasive tools like EEG. In an EEG, which is the most common method for measuring, electric brain signals produced by brain activities are monitored and documented using sensors [77]- [79]. Further, cells in the brain will align with each other and generate the electrical signal whose activity patterns can be analyzed.…”
Section: Cognitive and Affective Brain-computer Interfaces In Educationmentioning
confidence: 99%
“…The brain function's electromagnetic patterns can be detected using non-invasive tools like EEG. In an EEG, which is the most common method for measuring, electric brain signals produced by brain activities are monitored and documented using sensors [77]- [79]. Further, cells in the brain will align with each other and generate the electrical signal whose activity patterns can be analyzed.…”
Section: Cognitive and Affective Brain-computer Interfaces In Educationmentioning
confidence: 99%
“…Additionally, some signals that can effectively reflect the variation of the body’s movement can also be adopted for motion estimation, such as the surface electrocardiogram signal of the forearm [ 20 ] and foot pressure [ 21 ]. A change of scenario can also be effectively adopted for motion recognition, such as using the infrared sensor to detect temperature changes [ 22 ], distance sensors for capturing the distance between the equipment and object [ 23 ], pressure-sensitive devices mounted on the floor, EEG signal [ 24 ], ambient light to estimate gestures [ 25 ], and utilization of Wi-Fi, RF signals [ 26 ], and so on.…”
Section: Related Workmentioning
confidence: 99%
“…After surveying lung cancer patients, the authors of [75] concluded that QoL data should be studied at every visit for each patient and in-between visits. Since OT is intended to allow ADL independently [76], OT QoL monitoring metrics such as the type, length, and frequency of therapeutic exercises, and change in the difficulty level or course of activities is recommended to be personalized [77,78,79,80,81,82,83,84,85,86,87,88,89]. Moreover, data privacy, confidentiality, and integrity can be assured by leveraging the recent advancement in blockchain and off-chain-based decentralized solutions, which guarantees the availability and scalability of OT data, proper end-to-end encryption, a digital wallet with secure cryptographic public/private keys, and high-speed transaction overlays [90,91].…”
Section: System Designmentioning
confidence: 99%